2021
DOI: 10.1186/s12866-021-02335-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility, multilocus sequence typing, and virulence of listeria isolated from a slaughterhouse in Jiangsu, China

Abstract: Background Listeria monocytogenes is one of the deadliest foodborne pathogens. The bacterium can tolerate severe environments through biofilm formation and antimicrobial resistance. This study aimed to investigate the antimicrobial susceptibility, resistance genes, virulence, and molecular epidemiology about Listeria from meat processing environments. Methods This study evaluated the antibiotic resistance and virulence of Listeria isolates from sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…The STs identified in L. welshimeri were ST1005, ST1084, and ST168. This MLST results tally with two studies conducted in China ( 28 ) and Ireland ( 6 ) which showed the STs detected in the presumed nonpathogenic Listeria spp. were ST537, ST1005, ST1084, and ST168 belonging to L. innocua and L. welshimeri, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The STs identified in L. welshimeri were ST1005, ST1084, and ST168. This MLST results tally with two studies conducted in China ( 28 ) and Ireland ( 6 ) which showed the STs detected in the presumed nonpathogenic Listeria spp. were ST537, ST1005, ST1084, and ST168 belonging to L. innocua and L. welshimeri, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have shown L. monocytogenes can acquire resistance genes from the environment through plasmids and transposons, leading to the gradual increase in L. Monocytogenes resistance ( 6 , 40 ). Wu et al ( 28 ) showed Listeria carry multiple resistance genes tetA , tetM , ermA , ermB , ermC , and aac(6′)-Ib . Generally, resistant genes tetB and tetM are frequently detected in mobile plasmids ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hanes and Huang [ 62 ] reported that in the USA, from 2010 through 2021, data analysis identified fosX , lin , abc-f , and tet ( M ) as the four most common AMR genes found in L. monocytogenes. Compared with published reports on resistance genes in L. innocua , the distribution of the resistance genes varied considerably [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 98%
“…Variable frequencies of AMR genes have been reported in strains of L. monocytogenes , L. innocua , and other Listeria spp. [ 28 , 29 ]. Hosain et al [ 30 ] have highlighted the potential negative impact of AMR on therapy in feed animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Lincomycin and tetracycline are used for clinical practice to inhibit protein synthesis in bacteria. Previous studies showed resistance to lincomycin in L. monocytogenes isolated from foods in Italy (100%) and food processing environments in China (90%) (Mauro et al, 2007;Wu et al, 2021). Lincomycin inhibits protein synthesis by binding to the 50S ribosomal subunit (Papich, 2016).…”
Section: Discussionmentioning
confidence: 99%